2020
DOI: 10.29136/mediterranean.714929
|View full text |Cite
|
Sign up to set email alerts
|

Determination of effects of some fungicides used in hazelnut growing areas against Trichoderma species

Abstract: In this study, the effects of some fungicides (boscalid+kresoxim methyl, fluopyram+tebuconazole, sulphur ve tetraconazole) used for control of powdery mildew disease in hazelnuts on Trichoderma harzianum (11-TTR-2), T. hamatum (F4), T. atroviride (T-4-5) and T. asperellum (T-11-25) were evaluated under in vitro conditions. The study showed that all concentrations (0.25×, 0.5×, 1.0× and 2.0×) of the fungicides significantly reduced the mycelial growth, spore germination and germ-tube elongation of Trichoderma i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In addition, Trichoderma can help plants combat biotic and abiotic stresses by inducing systemic responses and promoting growth (Hidangmayum & Dwivedi, 2018) [13] . Research has also shown that Trichoderma enhances root growth and potassium availability, which improves the plant's ability to withstand abiotic stress during growth (Yildirim et al, 2020) [37] .  Role as a biocontrol agent: Trichoderma is effective in controlling soil-borne, airborne, and foliar pathogens, as well as post-harvest pathogens which cause severe diseases (Sharma et al, 2011) [28] .…”
Section: Trichoderma Asperellum: Available As Farm Root Trichiamentioning
confidence: 99%
“…In addition, Trichoderma can help plants combat biotic and abiotic stresses by inducing systemic responses and promoting growth (Hidangmayum & Dwivedi, 2018) [13] . Research has also shown that Trichoderma enhances root growth and potassium availability, which improves the plant's ability to withstand abiotic stress during growth (Yildirim et al, 2020) [37] .  Role as a biocontrol agent: Trichoderma is effective in controlling soil-borne, airborne, and foliar pathogens, as well as post-harvest pathogens which cause severe diseases (Sharma et al, 2011) [28] .…”
Section: Trichoderma Asperellum: Available As Farm Root Trichiamentioning
confidence: 99%